2000
DOI: 10.1007/s004420000459
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic induction in saplings of three shade-tolerant tree species: comparing understorey and gap habitats in a French Guiana rain forest

Abstract: The photosynthetic induction response under constant and fluctuating light was examined in naturally occurring saplings (about 0.5-2 m in height) of three shade-tolerant tree species, Pourouma bicolor spp digitata, Dicorynia guianensis, and Vouacapoua americana, growing in bright gaps and in the shaded understorey in a Neotropical rain forest. Light availability to saplings was estimated by hemispherical photography. Photosynthetic induction was measured in the morning on leaves that had not yet experienced di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 34 publications
1
33
1
1
Order By: Relevance
“…Changes in LMA were caused by changes in leaf thickness but not in density. Increases in LMA with increasing tree age or size are well documented [26,56,60,74,89]. Variations in LMA related to changes in leaf thickness have been also reported in numerous species [58].…”
Section: Leaf Morphology and Anatomymentioning
confidence: 80%
See 3 more Smart Citations
“…Changes in LMA were caused by changes in leaf thickness but not in density. Increases in LMA with increasing tree age or size are well documented [26,56,60,74,89]. Variations in LMA related to changes in leaf thickness have been also reported in numerous species [58].…”
Section: Leaf Morphology and Anatomymentioning
confidence: 80%
“…Classical patterns of response of leaves to changing light conditions were observed between trees at low and medium irradiance [1,12,21,26,39,46,57,58,61,63,66,67,74,86,90]. Leaf thickness and density, leaf dry mass per area and stomatal density increased with increasing irradiance pointing out the large leaf plasticity of the species.…”
Section: Leaf Morphology and Anatomymentioning
confidence: 87%
See 2 more Smart Citations
“…Photosynthetic induction occurs rapidly, in minutes (Rijkers et al, 2000), whilst photosynthetic adjustments can take days (Cai et al, 2005) and morphological alterations are observed after weeks or months (Ackerly, 1997). Within the plasticity possible for each successional state, plants adjust their pigments, photosynthesis, ultra-structure and anatomy in response to light (Oguchi et al, 2003;Rozendaal et al, 2006;Terashima et al, 2006;Sarijeva et al, 2007).…”
Section: Introductionmentioning
confidence: 99%